Gambaran Kondisi Sanitasi Terminal Kota Palembang Tahun 2025 : Tantangan, Solusi, dan Rekomendasi untuk Peningkatan Kualitas Layanan Publik - Fatimah Azzahra; Hendawati Hendawati; Intan Kumalasari (STIKES Columbia Asia Medan, 2025)
Terminal sanitation plays a crucial role in creating a clean, safe, and comfortable environment for public transportation users. This study aims to describe the sanitation conditions at Jakabaring Terminal, Palembang city, in the year 2025. The research employed a descriptive method with an observational approach. Data were collected through direct observation using a checklist that assessed four aspects of sanitation: environmental hygiene outside the building, hygiene of rooms and structures, sanitation facilities, as well as comfort and safety. The findings show that all four assessed aspects were below the required sanitation standards, with the following percentages: environmental hygiene outside (52%), hygiene of rooms and buildings (66%), anitation facilities (60%), and comfort and safety (57%). The low scores were caused by several factors, including substandard toilet conditions, lack of separated trash bins, inadequate ventilation and lighting, and the absence of first aid kits and fire extinguishers. The study concludes that the sanitation conditions at Jakabaring Terminal do not meet the standards of a healthy terminal. Greater attention and action are required from the terminal management and relevant authorities to improve sanitation quality and ensure user comfort.